“OPAK IMUT” DAN “OPAK MINI” SEBAGAI SOLUSI PENINGKATAN MUTU PRODUK CASSAVA CHIPS DI DESA SIDODADI KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH - Hesti nur'aini; Karona Cahya Susena; Ahmad Soleh (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2015)
Sidodadi village Pondok Kelapa Regency District of Central Bengkulu is one of the villages that have a great potential in the development of food processing industry. In the 1990s, the number of households cassava processing industry in this country reached 25 industry, but in 2000 the number of domestic industry's decline, until now there are only 5 households cassava processing industry. The objective of this community service program is to improve the skills, diversification of cassava chips products and improve the marketing system. Results showed that the diversification of activities and modification of cassava chips products at UD. Purwati and UD. Sugiono have a positive impact in terms of product quality, the level of consumer acceptance and production capacity. Packaging design improvements to increase consumer acceptance, so that the "Opak Imut" and "Opak Mini" which became a trademark of cassava chips partners production could reach a wider marketing network and can be consumed by children or family snacks and souvenirs.Keywords : Sidodadi Village, cassava chips, packaging, marketing